Impact of SCILL catalysts for the S–S coupling of thiols to disulfides. (20th September 2017) - Pavel, Octavian D.; Podolean, Iunia; Parvulescu, Vasile I.; Taylor, S. F. Rebecca; Manyar, Haresh G.; Ralphs, Kathryn; Goodrich, Peter; Hardacre, Christopher
Abstract : SCILL catalysts are active and selective for the S–S coupling of thiols to the corresponding disulfides showing a significantly increased stability. Abstract : This study reports the behaviour of SCILL based catalysts in the oxidative S–S coupling of aliphatic and aromatic thiols, namely 1-butanethiol and thiophenol, to dibutyl disulfide and diphenyl disulfide. A range of ionic liquids (1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide) and metal supported catalysts (5% Pt/SiO2 ; 5% Ru/SiO2 ; 5% Ru/C; 5% Pt/OMS-2) were used to prepare the SCILL catalysts and all were found to be active for the reaction following the trend 5% Pt-OMS-2 > 5% Pt/SiO2 > 5% Ru/C > 5% Ru/SiO2 . The presence of SCILL catalysts afforded high selectivity to the disulfide, and the activity of the SCILL catalyst was dependent on the ionic liquid used. A significant increase in the stability of all the supported metal catalysts was found in the presence of the ionic liquid, and there was no change in the selectivity towards disulfides. This demonstrated that the ionic liquids protect the active sites of the catalyst against sulfation, thus providing more stable and active catalysts.